2011
DOI: 10.1016/s2255-4971(15)30174-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Anterior Pain on Results From Anterior Cruciate Ligament Reconstruction

Abstract: Objective: To examine the impact of residual pain on functional outcomes two years after arthroscopic anterior cruciate ligament (ACL) reconstruction and compare the types of graft used during the procedure (patellar vs. flexor). Method: A retrospective epidemiological study on 129 ACL reconstructions with a mean follow-up of 28 months was conducted. The presence, intensity and location of the anterior pain were investigated. Pain provocation tests were conducted, sensitivity was analyzed and functional scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
0
6
0
2
Order By: Relevance
“…9,22,24 Assim como observado por outros autores, não houve diferença entre o uso dos enxertos quando foram avaliados pelo IKDC. [24][25][26] Jansson et al, 27 26 apresentaram em seu artigo prospectivo que não se observou diferença estatisticamente significativa na amplitude de movimento entre os grupos estudados, assim como neste trabalho.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…9,22,24 Assim como observado por outros autores, não houve diferença entre o uso dos enxertos quando foram avaliados pelo IKDC. [24][25][26] Jansson et al, 27 26 apresentaram em seu artigo prospectivo que não se observou diferença estatisticamente significativa na amplitude de movimento entre os grupos estudados, assim como neste trabalho.…”
Section: Discussionunclassified
“…9,25,27 No trabalho de Vasconcelos et al, 25 em pacientes nos quais se usou enxerto dos tendões flexores, a queixa álgica era principalmente na região medial. 25 Entretanto, outros estudos reportaram-se à ausência de diferença estatística na dor do joelho entre os enxertos usados, 15,18 similares aos resultados obtidos neste trabalho.…”
Section: Discussionunclassified
“…As also observed by other authors, no difference in graft use was observed when this was assessed using the IKDC scale. 24 , 25 , 26 …”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that patients present greater complaints of pain in the anterior region of the knee, particularly when kneeling down, when the patellar tendon is used as a graft. 9 , 25 , 27 In a study by Vasconcelos et al, 25 among patients in whom grafts from the flexor tendons were used, the complaints of pain were mainly from the medial region. 25 However, other studies have reported that there was no statistical difference in knee pain between the grafts used, 15 , 18 in the same way as seen in the results from the present study.…”
Section: Discussionmentioning
confidence: 99%
“…An improved surgical technique for reconstructing this ligament has made it less invasive, and when combined with early rehabilitation leads to joint stability and decreases the time patients need to return to their normal activities (not only professional sports, but particularly to work in ordinary patients), which has greatly increased the number of surgical reconstructions in recent years. 3 …”
Section: Introductionmentioning
confidence: 99%